The Saint - Brown, David; Evans, Roberts; Macdonald, William J.; Neufeld, Mace; Noyce, Philip; Kilmer, Val 1959-; Shue, Elisabeth 1963-; Serbedzija, Rade 1946- (Paramount, 1997)
An array of sophisticated gadgetry is at Templar's commnad as he plunges into a cloak-and-dagger netherworld of move and countermove. Cool, too, is Templar's knack for coming up with the right disguise at the right time.